Educação alimentar e nutricional: estratégias lúdicas facilitadoras do ensino de biologia na educação de jovens e adultos - Melo, Alena Sousa de (2019)
Youth and Adult Education (Educação de Jovens e Adultos – EJA) is a teaching modality marked by evasion and low learning indexes. Despite the several challenges, the subject of Biology in EJA has to be capable of connecting science, technology, health, environment and other themes necessary to the reception and full formation of the students. With the objective of promoting the scientific knowledge by playful moments in the Biology classes, the Food and Nutrition Education (Educação Alimentar e Nutricional – EAN) in EJA was chosen as a theme that aggregates several contents for the production of active methodologies in the learning facilitation and the rising of the student’s protagonism and authonomy. The study was developed at the Elementary and High Education State School Prof. José Baptista de Mello (EEEFM Prof. José Baptista de Mello), a state public school located in the city of João Pessoa – PB, in the evening classes of EJA 5th cycle, which has 96 registered students, with an average number of 60 attending ones. It has been opted for a quantitative and qualitative approach, using the ethnographic method with focus on participant observation. To the development of this study it has been applied pre-test questionnaire, which served as a base for the elaboration of the produced strategies. After the strategies application it has been applied post-test questionnaries, aiming to verify the relevance of the produced strategies. As a result, it has been produced five pedagogical strategies. The first one was represented as a Pedagogical Workshop, in which it has been developed two activities called Mitos X Verdade (Myths X True) and Nutriquiz. The second strategy was a game called Construindo uma Pirâmide Alimentar (Building a Food Pyramid), which was an investigation activity. The third one was a game called De olho no rótulo (Keep an eye on the label), whose objective was to guide the conscious reading of the food labels. The fourth strategy consisted on the application of a didactic sequence called Diversidade de microrganismos (Microorganisms diversity) which addressed themes related to food security and endoparasites, and the fifth one was the production of a play called O lipídio vai a júri popular (The lipid goes to popular trial), in which it has been opportunized the protagonism of the student in its elaboration. At the end of the execution, all the produced strategies were gathered in a pedagogical primer available in an online repository to serve as a collaboration to Biology teachers who work in EJA. The results obtained after the post-test show that, as a facilitating proposal for learning by motivation and contextualization of the contents in the students’ everyday life, the applied strategies have shown to be assertive and aligned to what it has been proposed in this study. It is concluded, throughout the observation and data obtained, that the participation and commitment of the students have improved after the strategies application, besides having also been verified the enlargement of the students perception in relation to the capacity of understanding the ecological, social, political and environmental dimensions which comprise the food culture.